The Moods of Marianne: Of Hijabs, Nikes, Implicit Religion and Post-Modernity - Ménard, Guy (Implicit religion, 2004)
Discusses the question of secularity in France in the perspective of a new law passed by the French government in 2004, that sets out to prohibit the presence of all religious symbols in the public sphere. Significance of the analogy between wearing Nike running shoes and wearing a Muslim veil from the perspective of implicit religion; Inquiry into the very limits of the definition of religion that underscores the very conception of modern secularity; Question of whether wearing Nikes is not essentially different from wearing a hijab.